Analisis Pengaruh Komposisi Polypropylene (PP) Terhadap Kekuatan Impact dan Kekerasan Komposit Bermatriks Epoxy - Kismanti, Shinta Tri; Waluyo, Marhadi Budi; Asriansyah, Ferdy (Faculty of Engineering, Universitas Borneo Tarakan, 2024)
In this study, the composite was reinforced with waste from instant noodle packaging consisting of polypropylene (PP) plastic. The creation of composites using PP as a filler was the purpose of this study. Impact and hardness testing were the composite variant without filler (100%/0%) and variation B (15%/10), with value of 80,5 Shore D and 67 shore D, accrding to analysis of research data. Particle addition composite materials’ impact strength could be increased by adding chopped plastic trash. With a composition of 15%/85% and an impact strength of 0.099 J/mm², composite variantion B had the maximum impact strength. When instant noodle wrapper plastic waste was combined with epoxy resin, a composite material was created. This matrials’ mechanical strength could be increased by increasing the instant noodle wrapeper fiber content and decreasing the epoxy resin composition this demonstrated that the primary filler for boosting mechanical strength was instant noodle wrapper fiber. The fibers in the instant noodle wrapper were what gave it iss increased mechanical strength, but because so much filler was employed, the interface between in and the matrix did not bind. The fiber would lift in a mechanical test.